Analysis of impedance measurements of a suspension of microcapsules using a variable length impedance measurement cell - Križaj Dejan (Journal of Electrical Bioimpedance, 2012)
Electrical impedance measurements of a suspension have to take into account the double layer impedance that results from a very thin charged layer formed at the electrode-electrolyte interface. A dedicated measuring cell that enables variation of the distance between the electrodes was developed to investigate the electrical properties of suspensions using two-electrode impedance measurements. By varying the distance between the electrodes it is possible to separate the double layer and the suspension impedance from the measured data. Electrical ‘lumped’ models have been developed from measured and extracted impedances. The error of non-inclusion of the double layer impedance has been analyzed. The error depends on the frequency of the measurement as well as the distance between the electrodes.